2018
DOI: 10.1016/j.jconrel.2018.05.016
|View full text |Cite
|
Sign up to set email alerts
|

Advances in the slow freezing cryopreservation of microencapsulated cells

Abstract: Over the past few decades, the use of cell microencapsulation technology has been promoted for a wide range of applications as sustained drug delivery systems or as cells containing biosystems for regenerative medicine. However, difficulty in their preservation and storage has limited their availability to healthcare centers. Because the preservation in cryogenic temperatures poses many biological and biophysical challenges and that the technology has not been well understood, the slow cooling cryopreservation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
45
0
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(52 citation statements)
references
References 132 publications
0
45
0
7
Order By: Relevance
“…To ascertain cell regrowth after freezing and thawing, 120 μl of each thawed solution was dispersed into 10 ml fresh YPD broth medium and incubated at 30 °C, 150 rpm. Aliquots were drawn at 8,12,24,28,32,48, 56 h and optical density at 600 nm was tracked using a UV spectrometer (UVIKONXL SECOMAM). Three replicates were performed for each ice front velocity.…”
Section: Methodsmentioning
confidence: 99%
“…To ascertain cell regrowth after freezing and thawing, 120 μl of each thawed solution was dispersed into 10 ml fresh YPD broth medium and incubated at 30 °C, 150 rpm. Aliquots were drawn at 8,12,24,28,32,48, 56 h and optical density at 600 nm was tracked using a UV spectrometer (UVIKONXL SECOMAM). Three replicates were performed for each ice front velocity.…”
Section: Methodsmentioning
confidence: 99%
“…Cryopreservation, known as a viable option for tissue preservation and storage, can have severe effects on the viability and function of tissues during the freezing/thawing processes and from use of cryoprotective agents [66]. Alginate microcapsules have demonstrated the ability to maintain structure, slow cooling process, reduce effects of ice crystal formation on tissue, and regulate influx of cryoprotective agents during cryopreservation [67,68]. First used in preservation of plant cells, use of an alginate coating has been observed to have cryoprotective properties [69][70][71][72].…”
Section: Cryoprotective Use Of Alginate Microencapsulationmentioning
confidence: 99%
“…Transplantation research has particularly benefited from use of alginate technologies during cryopreservation. Recent studies in pancreatic islet transplantation have demonstrated that use of alginate microencapsulation helps maintain islet viability during preservation and improves islet secretory function during transplantation [67,78,79]. A 10 years study using encapsulated rat, pig, human islets showed that alginate encapsulated islets maintained significantly higher viability, secretory function, and yield compared to nonencapsulated islets after cryopreservation for 10 years [80].…”
Section: Cryoprotective Use Of Alginate Microencapsulationmentioning
confidence: 99%
“…La crioprotección consiste en la adición previa a la congelación, de una sustancia que es capaz de incorporarse a las células del tejido o a los espacios intracelulares, protegiendo la textura del material vegetal del daño causado por los cristales de hielo (Gurruchaga et al 2018). Los crioprotectores son sustancias penetrantes o no penetrantes, de diferentes pesos moleculares, de baja toxicidad, que disminuyen el punto de congelación de una solución; con la aplicación de un crioprotector, las células estarán más deshidratadas y el gradiente osmótico al que estarán sometidas será menor (Pérez et al 2016).…”
Section: Introductionunclassified
“…Grandes progresos se lograron con el desarrollo de técnicas de crioprotección, identificándose este campo como un área de prioridad para la investigación, desarrollo y transferencias de tecnología. Se han llevado a cabo investigaciones que evalúan la capacidad de protección de células vegetales y animales de diferentes criopotectores (Marco & Serrano, 2012;Gurruchaga et al 2018). En tejido animal, se ha reportado el efecto crioprotector de oligopéptidos obtenidos de hidrolizado de merluza y de colágeno, con aplicaciones en la crioprotección de pescado y en la protección a la desnaturalización de la proteína de Surimi.…”
Section: Introductionunclassified